Hybrid Tamm and surface plasmon polaritons in resonant photonic structure. (September 2020) - Bikbaev, Rashid G.; Vetrov, Stepan Ya; Timofeev, Ivan V.
Highlights: The possibility of the hybrid TPP-SPP modes excitation in resonant photonic crystal structure is shown. The localization of the field at the wavelength of hybrid modes is investigated. The possibility of controlling the spectral properties of hybrid modes by changing the volume concentration of nanoparticles and the angle of incidence of radiation on the structure is demonstrated. The formation of hybrid modes in the case of conjugation of a photonic crystal with an anisotropic nanocomposite film is demonstrated. A model of an optical sensor on TPP-SPP modes is proposed. Abstract: Hybrid modes originating from the coupling of the Tamm and surface plasmon polaritons excited in a one-dimensional resonant photonic structure are demonstrated. The structure represents a photonic crystal bounded by a nanocomposite film consisting of a transparent matrix and silver nanoparticles uniformly distributed over its volume. In comparison with structures on planar metal films the volume concentration and shape of nanoparticles are of great help in configuring the hybrid mode properties, including their wavelength and splitting. Also the radiation incidence angle variation opens the possibility of fine-tuning the energy spectra of the structure. We demonstrate the high-sensitivity of optical sensors based on the resonant photonic structure.